PENGARUH PERSON ORGANIZATION FIT DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI - Dwi Pandega Winata; Suhana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to find empirical evidence of the effect of person organization fit and perceived organizational support on employee performance through organizational commitment. The object of the research is at the Surabaya City Disaster Management and Community Protection Agency. The population was 143 respondents. The sampling technique was the census method, which means that the entire population is the sample of the research. The data analysis tool uses multiple linear regression. The results show that there are positive and significant effect between PO-Fit and perceived support toward organizational commitment. The other finding, there is a positive and significant effect between organizational commitment, perceived organizational support and partial organizational commitment on employee performance. The results of the first mediation effect test show that organizational mediation commitment influences PO Fit on employee performance. While the results of the second mediation effect test found that organizational mediation commitment influences perceived organizational support on employee performance. The study has theoretical and practical implication.